Solvent-free Synthesis and Characterization of Cu(II), Co(II) and Ni(II) Complexes of 2-(3-phenylallylidene) thiosemicarbazide - Aguzue, Onyinye Chinelo; Oviawe, Amowie Philip; Olajide, Olutayo Olawumi; Afolayan, Michael Olalekan; Adedirin, Oluwaseye (Journal of Science and Mathematics Letters, 2021)
Mechanochemical solvent-free synthesis of Cu, Co and Ni complexes of 2-(3-phenylallylidene) thiosemicarbazide is described. The mechanochemical products were characterized on the basis of solubility, melting point, conductivity, FTIR, UV-Visible, GC-MS, 1H-NMR and 13C-NMR. The Schiff base ligand and its metal (II) complexes are coloured stable compounds. The solubility test shows that the compounds are soluble in dimethylsulphoxide, dimethexylformamide; partially soluble in ethanol and insoluble in water. The melting points of the compounds were within the range of 179 oC to 183 oC. The UV-Visible electronic spectra data showed the different transfers and transitions in the ligand and metal complexes. The different absorptions in the electronic spectra also predicted the possible structures of the complexes. The 13C-NMR and 1H-NMR showed the different carbon and hydrogen environments in the ligand. The GCMS confirmed the structure of the ligand and exhibited different fragments. The antimicrobial activities of the ligand were enhanced with the metal complexes and the results were very interesting as the complexes showed good antifungal and antibacterial activities.